The contraction modalities in a stretch-shortening cycle in animals and single joint movements in humans: A systematic review - Groeber, M.; Reinhart, L.; Kornfeind, P.; Baca, A. (Journal of Sports Science & Medicine, 2019)
A systematic literature search was conducted to review the force-enhancing mechanisms caused by a stretch-shortening cycle (SSC). The review aims to yield an overview of the contraction modalities influencing the SSC performance in animals and single joint movements in humans. The search was executed in common with the PRISMA statement. CINAHL, MEDLINE (via ProQuest), PubMed, ScienceDirect, Scopus and Web of Science databases were used for the systematic search from its inception until February 2019. A quality assessment was conducted with a modified Downs and Black checklist. Twenty-five studies were included. SSC effects, leading to increased force/work during a SSC and a reduced force depression (FD) compared to a pure shortening contraction, are existent on different levels of the muscle, from single fiber experiments to the level of in vivo muscle-tendon complex. Muscle performance is dependent on shortening velocity, shortening distance, stretch distance, the time (transition phase) between stretch and shortening and the active prephase duration. Concerning stretch velocity we found conflicting results. The findings from this systematic review indicate that the mechanisms in the early phase of shortening are associated with pre-activation effects, elastic recoil and stretch reflex. Furthermore, we speculate that residual force enhancement (RFE) is mainly responsible for an increased steady-state force compared to a pure shortening contraction. Key Points